Transferring clinically established immune inflammation markers into exercise physiology - Walzik, David; Joisten, Niklas; Zacher, Jonas; Zimmer, Philipp (Technische Universität Dortmund, 2021)
Over the last decades the cellular immune inflammation markers neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and systemic immune-inflammation index (SII = NLR × platelets) have emerged in clinical context as markers of disease-related inflammation and are now widely appreciated due to their integrative character. Transferring these clinically established inflammation markers into exercise physiology seems highly beneficial, especially due to the low temporal, financial and infrastructural resources needed for assessment and calculation. Therefore, the aim of this review is to summarize evidence on the value of the integrative inflammation markers NLR, PLR and SII for depiction of exercise-induced inflammation and highlight potential applications in exercise settings. Despite sparse evidence, multiple investigations revealed responsiveness of the markers to acute and chronic exercise, thereby opening promising avenues in the field of exercise physiology. In performance settings, they might help to infer information for exercise programming by reflecting exercise strain and recovery status or periods of overtraining and increased infection risk. In health settings, application involves the depiction of anti-inflammatory effects of chronic exercise in patients exhibiting chronic inflammation. Further research should, therefore, focus on establishing reference values for these integrative markers in athletes at rest, assess the kinetics and reliability in response to different exercise modalities and implement the markers into clinical exercise trials to depict anti-inflammatory effects of chronic exercise in different patient collectives.
focus on neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and systemic immune-inflammation index
European journal of applied physiology;Vol. 121. 2021, pp 1803–1814
Keywords: Physical activity; Exercise; Training; Recovery; Inflammation; Biomarker; 796; Biomarker; Sport | Training |; Bewegung |; Entzündung |; Genesung |